Gallic acid content and antioxidant mechanism are responsible for the antiproliferative activity of ‘Ataulfo’ mango peel on LS180 cells - Velderrain Rodríguez, Gustavo (2018)
Mango “Ataulfo” peel is a rich source of polyphenols (PP), with antioxidant and anti-cancer properties; however, it is unknown whether such antiproliferative activity is related to PP’s antioxidant activity. The content (HPLC-DAD), antioxidant (DPPH, FRAP, ORAC), and antiproliferative activities (MTT) of free (FP) and chemically-released PP from mango ‘Ataulfo’ peel after alkaline (AKP) and acid (AP) hydrolysis, were evaluated. AKP fraction was higher (µg/g DW) in gallic acid (GA; 23,816 ± 284) than AP (5610 ± 8) of FR (not detected) fractions. AKP fraction and GA showed the highest antioxidant activity (DPPH/FRAP/ORAC) and GA’s antioxidant activity follows a single electron transfer (SET) mechanism. AKP and GA also showed the best antiproliferative activity against human colon adenocarcinoma cells (LS180; IC50 (µg/mL) 138.2 ± 2.5 and 45.7 ± 5.2) and mouse connective cells (L929; 93.5 ± 7.7 and 65.3 ± 1.2); Cheminformatics confirmed the hydrophilic nature (LogP, 0.6) and a good absorption capacity (75%) for GA. Data suggests that GA’s antiproliferative activity appears to be related to its antioxidant mechanism, although other mechanisms after its absorption could also be involved